Religion and Politics in America: Faith, Culture, and Strategic Choices - Hertzke, Allen D. (Routledge, 2018)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- List of Illustrations -- Preface -- 1 Religion and Political Culture in America: From the Historical Legacy to the Present Day -- The Puritan Temper -- Religious Freedom and Pluralism -- The Evangelical Dimension -- The Populist Dimension -- Spiritual and Religious Individualism -- Conclusion -- Discussion Questions -- Further Reading -- Notes -- 2 Theories of Religion, Culture, and American Politics -- Civil Religion -- The Unconventional-Partners Thesis -- Culture Wars -- The Secularization Thesis -- Populism -- The Religious-Marketplace Thesis -- The Culture-Shift Thesis -- Conclusion -- Discussion Questions -- Further Reading -- Notes -- 3 Christianity and Its Major Branches -- The Status of Religion in the United States -- Evangelical Protestantism -- Mainline Protestantism -- Roman Catholicism -- Conclusion -- Discussion Questions -- Further Reading -- Notes -- 4 Judaism, Islam, and Other Expressions of Religious Pluralism -- Jews and Judaism -- Muslims and Islam -- The LDS Church: A Uniquely American Christian Faith -- Separatist Religions -- Other Small Religions -- Secular and Other Disaffiliated Americans -- Conclusion -- Discussion Questions -- Further Reading -- Notes -- 5 Latino and African-American Religion and Politics -- The Changing Status of Latino Religion -- Latinos in Public Life -- African-American Religion and Politics: Toward a Broader View -- History and Black Political Attitudes -- Connections between Black Religion and Politics -- Islam in the African-American Community -- Conclusion -- Discussion Questions -- Further Reading -- Notes -- 6 Gender, Sexual Orientation, Religion, and Politics -- Gender and Religion in American Life -- Women's Diverging Perspectives on Religion and Politics -- The Politics of Women in the Pews